Factors Affecting Behavioral Intention of Delivery Drones During the COVID-19 Pandemic - Hendarno, Ari; Med Irzal (Universitas Negeri Jakarta, 2023)
Delivery of goods which is usually done by face to face is advised not to do. Physical distancing is recommended by World Health Organization (WHO). Physical distancing helps limit the spread of COVID-19 this means we keep a distance of at least 1m from each other and avoid spending time in crowded places or in groups (WHO, 2020). A possible alternative is to make deliveries using drones. It can keep the sender and receiver from seeing each other face to face. The final decision on using the drone delivery service rests with the customer. This will be closely related to customer's behavioral intention. This study aims to find out what factors influence behavioral intention to use drone delivery during the COVID-19 pandemic. The factors analyzed were function, cognition, hedonic motivation, incentive, social benefits, and health benefits. These factors are tested and analyzed which influences behavioral intention. The results obtained are function, cognition, and health benefits. The significance level in this study is 0.1 with a limit T-value of 1.29007.